2020
DOI: 10.1055/s-0040-1714768
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of The Nasal Symmetry in Unilateral Cleft Lip And Palate Patients Treated With Nasoalveolar Molding

Abstract: Background Nasoalveolar molding (NAM) has been extensively used as a presurgical technique in the treatment of unilateral cleft lip and palate (UCLP) over the last two decades. It has proven to be a useful tool to reduce the cleft size, improve nasal symmetry, and increase the columellar length. The long-term stability of these findings has not been conclusively proven. Methods In this longitudinal study, the nasal symmetry of 24 NAM treated UCLP patients was evaluated to assess the 5-year stability of NAM. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The idea of using presurgical orthopedics is to improve the symmetry of the upper arch 5 and enhance the symmetry of the immature nasal cartilage through nasal stents before the primary surgery. 10,30 In this context, the evaluation of the changes that the NAM protocol promotes, or the consequences of its absence, in nasal and maxillary symmetry seeks to confirm its importance, providing evidence for choosing the best treatment available for the child with a cleft. This study found that the treatment with NAM through the reverse engineering technique yielded maxillary and facial growth effects towards better symmetry in patients with complete UCL/P.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea of using presurgical orthopedics is to improve the symmetry of the upper arch 5 and enhance the symmetry of the immature nasal cartilage through nasal stents before the primary surgery. 10,30 In this context, the evaluation of the changes that the NAM protocol promotes, or the consequences of its absence, in nasal and maxillary symmetry seeks to confirm its importance, providing evidence for choosing the best treatment available for the child with a cleft. This study found that the treatment with NAM through the reverse engineering technique yielded maxillary and facial growth effects towards better symmetry in patients with complete UCL/P.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1950s, different techniques have been presented to bring soft and hard tissue closer together 3,4 . The nasoalveolar molding (NAM) technique is a treatment modality described by Grayson et al, 5 which seeks to alleviate asymmetries and cleft severity before surgery 6–8 while promoting important modifications on immature nasal cartilage, taking advantage of its malleability 9,10 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing nasolabial aesthetics in BCLP patients using the anatomic subunit scale, we found that the immediate (6-month) aesthetic results were significantly better in those who had nasoalveolar molding [44] . Unfortunately, this was not a randomized study, and there was no power calculation to determine the sample size.…”
Section: Limitationsmentioning
confidence: 91%
“…The literature suggests relapse is apparent in the first postoperative years [43][44][45] . Practitioners believe that primary rhinoplasty is warranted as an adjunct to NAM.…”
Section: Limitationsmentioning
confidence: 99%